Youth Friendly Needs Assessment - Artz, Sibylle; Nicholson, Diana; Halsall, Elaine; Larke, Susan (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper describes the development of a needs assessment guide that is user-friendly, facilitates the development of the youth-counselor relationship, and is sensitive to gender, sexual orientation and cultural diversity. Through a three-phase collaborative process with counselors and youth, the major issues in needs assessment were uncovered and a youth sensitive needs assessment guide that supports a strong positive working alliance between counselor and youth was developed. The project highlights the importance of involving youth in assessing their own needs. Suggestions for supporting workers in needs assessment activities are provided. The needs assessment guide and background information on the development project are available on-line at http://web.uvic.ca/cyc/naty